A Concept Analysis of Resistiveness to Care. (January 2021) - Spigelmyer, Pamela C.; Hupcey, Judith; Kitko, Lisa
People with cognitive impairment often require assistance with activities of daily living. It is when providing assistance with these activities that many caregivers experience behaviors that have been categorized as disruptive or problematic and called resistiveness to care. These behaviors are considered to be a source of burden and job burnout for caregivers. Nurses wanting to help caregivers, who manage these trying situations, need to understand the concept of resistiveness to care and communicate this knowledge clearly with health care providers. Therefore, a literature search was conducted in 2012 within the databases CINAHL, Medline (PubMed), ProQuest, and PsychINFO. This produced 40 relevant articles. Because no concept analysis existed for resistiveness to care, a principle-based concept analysis was performed. The analysis helped construct a theoretically defined concept. Further analysis highlighted that more research is needed to advance the concept of resistiveness to care to enhance professional communication surrounding this phenomenon.